Hubungan Antara Nilai Prestasi Belajar Siswa pada Mata Pelajaran Aqidah Akhlak dengan Kepatuhan Terhadap Tata Tertib Madrasah - Hanik Mufaridah; Wawan Juandi (Fakultas Dakwah Universitas Ibrahimy, 2023)
Aqidah morality as a field of study, is a lesson that discusses morals or everyday beha vior. Whether or not a person’s behavior in the madrasa can be seen from his adherence to the rules at the madrasa. This research is a quantitative research with correlational type. The results show that there is no relationship between the value of student achievement in the subject of Aqidah Morals with adherence to the rules of Madrasah or the relationship betwe en the two is not significant. This can be caused by the validity of the research instruments that are not in accordance with the research hypotheses, theoretical studies and relevant re search results. In addition, considering other possible variables as control variables, to find out whether after the control the scores of the two groups have a significant relationship or not. And obtained the price of the correlation coefficient of 0.162 (positive) with a probabi lity of error (Sig.) of 0.217 which is greater than 0.05. This means that there is no relations hip between the value of student achievement in the subjects of aqidah morality with adhe rence to the rules of Madrasah.